2020
DOI: 10.31925/farmacia.2020.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Internships in Pharmaceutical Students’ Development

Abstract: The primary purpose of a pharmacist today, is, as it usually has been, to be in the service of human health. This aim can be achieved through a large number of professional possibilities. In this context, pharmacy students need a wide variety of skills, in addition to basic biology and chemistry notions. The main objective of this paper is to explore how should pharmacy higher education institutions in Romania adapt so that they prepare graduates to make the transition from academic training to joining the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In addition, this type of dilemma was common amongst the participants in the study conducted by Chaar et al [5]. Results of this study showed that pharmacists need to make "the choice between what is in the best interest of the patient, or ensuring no harm is done to the patient, and what the doctor prescribed", also pharmacists found difficult to choose a course of action [5].…”
Section: Table III Proposed Situations With Ethical Issuesmentioning
confidence: 93%
See 4 more Smart Citations
“…In addition, this type of dilemma was common amongst the participants in the study conducted by Chaar et al [5]. Results of this study showed that pharmacists need to make "the choice between what is in the best interest of the patient, or ensuring no harm is done to the patient, and what the doctor prescribed", also pharmacists found difficult to choose a course of action [5].…”
Section: Table III Proposed Situations With Ethical Issuesmentioning
confidence: 93%
“…In addition, this type of dilemma was common amongst the participants in the study conducted by Chaar et al [5]. Results of this study showed that pharmacists need to make "the choice between what is in the best interest of the patient, or ensuring no harm is done to the patient, and what the doctor prescribed", also pharmacists found difficult to choose a course of action [5]. However, the results showed that this ethical issue ("A pharmacist dispenses a medicine he/she personally considers inadequate for the therapeutic treatment of the patient, in order to avoid any conflicts with the physician") indicates unsatisfactory communication between physicians and pharmacists.…”
Section: Table III Proposed Situations With Ethical Issuesmentioning
confidence: 99%
See 3 more Smart Citations